A strength reliability calculation method of tip relief gears - Hongbing Wang; Jun Xiao; Lairong Yin; Bo Hu; Huihua Liu (PLoS ONE, 2026)
The gear tip relief affects the root bending stress and the contact pressure, which affects the strength reliability of the gear system. In this work, based on the proposed tip relief model and the mesh model of the gear pair, incorporating the gear’s contact strength and bending strength models together with the stress–strength interference theory, a strength reliability model of tip relief gears was established by assuming that both the stress and strength follow a normal distribution. The results indicate that the tip relief reduces the meshing impact and increases the strength reliability. Then, the effects of the modification length, the modification height, and the applied load on the gear strength reliability were analyzed. It was found that with the increase in gear modification length and the modification height, both the contact and bending strength reliability at the engaging-in and the recession points decrease compared to the standard gears. Additionally, an increasing of the load also results in a decline in gear strength reliability. Therefore, the rational control of the gear loading and the appropriate selection of modification length and modification height are of great significance in reducing meshing impact while ensuring the strength reliability of gears.